FEATURES OF CHILDREN'S FEAR AT A DENTAL APPOINTMENT - PhD. Ortikova Nargiza Khayrullaevna (Journals Park Publishing, 2024)
The problem of anxiety occupies a special place in modern scientific knowledge. It is the subject of a considerable amount of research, not only in psychology, but also in medicine, physiology, philosophy and sociology.
Keywords: competition anxiety, psychophysiological level, problem of anxiety, emotional phenomena.